Fear of fraud and willingness to pay for hybrid maize seed in Kenya. (July 2021) - Gharib, Mariam H.; Palm-Forster, Leah H.; Lybbert, Travis J.; Messer, Kent D.
Highlights: This field experiment tests whether concerns about fraud reduce WTP for hybrid maize seed in Kenya. Farmers are willing to pay 15% more for hybrid seed purchased directly from the seed company. Untrained farmers are less likely to infer anything about seed quality from packaging features. Training on buying quality seed decreases farmers' WTP for damaged bags by 15%. Concern about fraud increases premiums for seed purchased directly from the company. Abstract: Concerns about poor seed quality and outright fraud in seed supply chains can reduce farmers' willingness to invest in hybrid seeds and in complementary inputs that increase crop yields and improve food security. In Kenya, seed companies have started marketing their seed using novel packaging features to signal product quality and authenticity. We use experimental auctions with smallholder farmers in Kenya's Nyanza Province to assess (1) farmer willingness to pay (WTP) for hybrid seed from different sources with different packaging features and (2) how WTP is affected by training on best practices for purchasing seed. We elicited demand for two popular types of hybrid maize seed and a familiar local (non-hybrid) seed. For each hybrid, we examined WTP for one bag purchased directly from the seed company and three bags purchased from local retailers, two of which had compromised packaging. Across both the control and training groups, participants were willing to pay a 15% premium, on average, for bags purchased directly from the seed company compared to mint condition bags purchased from local retailers. Without the training on purchasing seed, farmers did not discount compromised bags; however, farmers who received the training, were willing to pay 15% less for compromised bags. Education and outreach may be required for packaging innovations to increase investments in high-quality hybrid seed that can help enhance the productivity of smallholder farmers.